Aplikasi Sistem Informasi Social Media Advertise Maintenance Menggunakan Pendekatan Object Oriented Methodology - Sri Rahayu; Ryanthika Serliyanthi Setyaningrum; Yuni Kristina Dewi (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2021)
Information systems built in the form of social media and the internet make us able to carry out various activities without having to meet face to face. Social media is currently the main attraction for people to communicate and find information quickly. This is a great opportunity for companies to reach and expand their market. With an information system built in the form of social media and the internet, all obstacles, both distance and high costs, can be suppressed and communication can be carried out effectively. So far, PT. Red Eye Utama conducts marketing through radio advertisements, newspapers / billboards, this is what causes problems, due to limited space and time, as well as high costs to carry out all these processes. The negotiation process between the company and the customer is one of the obstacles that affects the company's service to customers. Therefore, one solution to the problems in this system is to build a Social Media Advertise Maintenance Information System. By using PIECES method analysis for improvements based on performance indicators, indicator information, economic indicators, control indicators, efficiency indicators and service indicators. To design the new system, object-oriented modeling is used, namely UML (Unified Modeling Language) which is the right tool to use in describing the system design that will be made according to User needs.